(untitled) (Research, Society and Development, 2021)
Lynxacarus radovskyi, one of the main mites that affect felines, is a Sarcoptiform that belongs to the Listophoridae family. It is characterized for being an important cause of dermatopathy, in which most cases present in the subclinical form, and the clinical manifestations are proportional to the amount of mites in the animal, transmitted mainly through fomites and direct contact; the clinical signs routinely observed are alopecia, scaling, easily piled hair, pruritus, and miliary dermatitis. The present work aimed to report the occurrence of Lynxacarus radovskyi, its symptomatological aspects and the established treatment, in a group of 26 domestic cats, coming from a commercial cattery, in the city of Porto Velho - RO, since there is no other report prior to this one. in the State. The treatment of the animals was carried out with baths of Amitraz and the spraying of Fipronil Spray®, weekly, within 30 days, proving to be effective for the elimination of the agent, with healthy animals at the end of the treatment period.